'Salve, risueña mentira': Cosmic Hyperbole, Confession and Historical Consciousness in Ramón del Valle-Inclán's Sonata de invierno (1905). Issue 6 (3rd July 2019) - Torres Cacoullos, Anna
Abstract: In Ramón del Valle-Inclán's Sonata de invierno (1905), a Prelate suggests to the Marqués de Bradomín that he write a book about his life, with the warning, however, that St Augustine and Rousseau are two different models for Bradomín's life story. This article proposes to read Sonata de invierno as confession, as opposed to memoir or autobiography, where 'Valleinclanian' confession in the mode of what I term 'cosmic hyperbole'—lies, exaggeration and storytelling—engages with both the worldly and sinful dimension of St Augustine's and Rousseau's Confessions . Cosmic hyperbole achieves historical consciousness, leading to a deeper and swelling understanding of the history of a whole culture (Spain's) and informing the rapport between history and meaning. When one lifts the fool's cap, rejecting the idea that history is meaningless, and ignorance is bliss, one encounters truth and lying as bedfellows. For Bradomín, getting in touch with one's history involves taking the 'truth-giving lie' to gain an ever-creating life. Bradomín's closed immediate society, wholly sacralised, and a humane, desacralized Spain are engaged in a Hegelian contest to the death of one: for Valle-Inclán, I will argue, it is, hopefully, of the former.